Salman Al-Muhammadi and His Narrations in the Prophetic Biography Through the Book "Al-Tabaqat Al-Kubra" by Ibn Sa’d (d. 230 AH) - An Analytical Study - Hussein, Dr. Maha Abdulrahman (Thi Qar Arts Journal, 2025)
Studying historical figures is one of the most prominent and important research areas for understanding historical events and the causes of major transformations in making historical events. This study focuses on one of the most prominent Islamic figures, the companion Salman Al-Farsi Al-Muhammadi (t), which has raised many questions about the accuracy of the events that accompanied his journey. Despite many studies on his life, many aspects mentioned remain shrouded in mystery, and many events that accompanied his life (t) need further study. This study reviews his life (t) and the most controversial events, along with the most important narrations about him in the fields of history and the prophetic biography, and the impact of historical events. It also examines how he paved his way in transmitting knowledge and investigating historical events, preceding the most prominent modern schools known for experimental science and learning through experience. The study then addresses the most important life milestones until his death